Tic Severity and Psychological Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The relationship between tic severity and neuropsychological function was examined in 12 monozygotic twin pairs with Tourette's syndrome at the National Institute of Mental Health, Bethesda, MD.